Cerebral achromatopsia in monkeys. - Heywood, C; Gaffan, D; Cowey, A (1995)
In human cerebral achromatopsia, extrastriate cortical damage produces a severe or complete loss of colour vision, with relative sparing of non-chromatic vision. The critical lesion appears to be in a medial occipito-temporal area, occupying the lingual and caudal fusiform gyri; positron emission tomography has shown that this cortical region is one of several activated in normal human observers during colour vision tasks. Attempts to find an analogous 'colour centre' in the cortex of monkeys have not been successful. In particular, ablation of cortical area V4, sometimes thought on physiological grounds to be more involved in wavelength and colour coding than any other visual cortical area, produces only mild impairments in colour discrimination. In the present study we tested the colour vision of monkeys after cortical ablations that mainly or entirely spared area V4. One group of monkeys (group AT) received ablations in the temporal lobe anterior to area V4, and a second group (group MOT) received ablations in a medial occipito-temporal area roughly corresponding in cranial location to the lesion that produces human cerebral achromatopsia. The animals in group MOT showed no impairment of their colour vision. Group AT, in contrast, had a severe impairment in chromatic vision, with a relative sparing of non-chromatic vision. Their behaviour was indistinguishable from that of a human patient with total cerebral achromatopsia who had been tested on the same tasks. These results show that area V4 in macaque monkeys is not analogous, and probably not homologous, to the human colour centre. Instead, they suggest that the area of the monkey's brain corresponding to the colour area in the human brain is in the temporal cortex, anterior to area V4.